Gender features of the Kazakhstan labour market in the context of sustainable development - Nyussupova, Gulnara; Aidarkhanova, Gaukhar; Kenespayeva, Laura; Kelinbayeva, Roza (Hungarian Geographical Bulletin, 2023)
Kazakhstan is demonstrating its commitment to promoting gender equality and working closely with the global community. Over the past decade, the gender gap in the structure of labour force of Kazakhstan has slightly decreased. However, gender gaps persist. Women in Kazakhstan make up slightly more than half of the total population of the country, but their contribution to indicators of economic activity, growth and well-being of republic is significantly below their potential. In this article, gender dynamics of Kazakhstan labour market are explored at macro and micro levels using GIS. In this article, authors tried to answer the following questions: What is the gender situation in the labour market of Kazakhstan, as a country of Central Asia region with an Eastern mentality? Does the growing number of employed women lead to higher levels of gender equality in the Kazakhstan labour market? What are the characteristics of women’s employment compared to men’s? The results of research show that women’s increased access to jobs has not led to a significant reduction in the gap in earnings and incomes between men and women. This is due to the gender segregation of vocational education, which lays the foundation for sectoral differentiation of employment with different geographical distributions. Also, the so-called “glass ceiling” or low accessibility to leadership positions hinders women’s greater competitiveness. In addition, such an important element of labour market as unpaid domestic work, which is mainly occupied by women, is still not recognized.